2007
DOI: 10.1016/j.ijgo.2007.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards mode of delivery and cesarean on demand in Turkey

Abstract: In the two groups studied the preference for cesarean delivery is higher in Turkish healthcare providers than in the public population. In both groups the attitude towards cesarean delivery on demand is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
(7 reference statements)
2
20
0
1
Order By: Relevance
“…In addition, there is a plan to prepare a new informed consent form that will explain that a C/S should not be performed unnecessarily. 20,[23][24][25][26][27][28][29][30][31] These findings are consistent with the literature. Finally, the health ministry has started a motherfriendly hospital programme.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, there is a plan to prepare a new informed consent form that will explain that a C/S should not be performed unnecessarily. 20,[23][24][25][26][27][28][29][30][31] These findings are consistent with the literature. Finally, the health ministry has started a motherfriendly hospital programme.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is reinforced by the observation of McGurgan, Coulter-Smith and O’Donovan, [35] who reported a strong association between a personal preference of obstetricians for Cesarean section and the Cesarean section rates in the hospitals in which they worked. Koken et al [20] raised the hypothesis that healthcare professionals who prefer Cesarean sections for their own pregnancies are less tolerant of the risks that vaginal delivery represents for the fetus. In addition, Hopkins [11] conducted a qualitative study in Brazil and reported that many physicians in the country, despite outwardly defending vaginal delivery, do not usually wait for delivery to progress naturally and anticipate the line of action even when no relevant clinical indications are present.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, in one of the pioneering studies conducted on this subject, Al-Mufti, McCarthy and Fish [19] reported that 17% of obstetricians participating in a study in London preferred a Cesarean section even when no complications were present. Interviews conducted in a hospital in Turkey in 2007 [20] found that more than half the healthcare professionals (physicians, nurses, midwives and laboratory technicians) believed that Cesarean sections were safer for the baby. In Norway, a study conducted in 2008 found that more than a quarter of obstetricians/gynecologists had already been submitted to a Cesarean section compared to a rate of only 12% in the general population [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies that have been conducted in Turkey indicated causes of women's vaginal delivery preference. These causes was; handle the sense of control, a desire for vaginal delivery experience, and a desire for early recovery and early discharged from hospital, a lower complication rates, fear of anesthesia and operation, safety of mother, better relationship to baby, less painful period after giving birth, the thoughts of 'better for the health' and 'birth is a normal event' and immediate breast feeding [8,9].…”
Section: Discussionmentioning
confidence: 99%